THE IMPACT OF E-LEARNING WITH (SYAM-OK) DURING PANDEMIC ON ENGLISH LEARNING RESULTS OF STUDENTS AT ELECTRONIC ENGINEERING EDUCATION DEPARTMENT OF MAKASSAR STATE UNIVERSITY - Samad, Putri Ida S. (JURNAL NALAR PENDIDIKAN, 2021)
The COVID-19 pandemic, which began in early 2020, had an impact on all industries, especially education. The government issued an order requiring students to study at home and thus eliminating face-to-face learning. Distance learning or online is a good solution to continue the learning process. This type of learning is referred to as e-learning. The research goal was to see how e-learning with (SYAM-OK) affected the value of learning for English courses at Makassar State University Department of Electronic Engineering Education, Faculty of Engineering. This population study consists of 125 students from the Department of Electronic Engineering Education, Faculty of Engineering, Makassar State University, who are enrolled in the S1, D4, and Vocational Mechatronics Study Programs. The sampling technique was purposive sampling, namely 85 students who programmed even semester English courses. Ex-post facto research with a quantitative descriptive method was used. According to the regression equation y = 14.888 + 0.812x, there is a 0.785 effect of e-learning with (SYAM- OK) on the value of learning results. This correlation value indicates that the two variables have a strong relationship. The calculated f value is 133.560, and the f table value is 3.956 (df1=1; df2=83). The regression correlation analysis revealed that 61.7 % of the influence of the e-learning variable (SYAM-OK) on the value of learning outcomes was influenced by other factors, while 38.3% was influenced by other factors.